Development of Sway Angle Measurement System - Wan Mohd Aizuddin Bin Wan Doshah, Wan Mohd Aizuddin (Universiti Teknologi Petronas, 2009)
Sway load control system is an important technology in the crane transportation industries. Researchers have developed these systems in order to increase crane transportation efficiency. However, a major problem in the research and development of the sway load control system is in providing a quick and accurate feedback on the sway angle. The objective of this project is to develop an effective way in the load sway angle measurement. To achieve the objective, several possible design alternatives will be studied. The project will go through into research, designing the system and possibly demonstrate an experiment in the laboratory for validity of the system. Finally, the best design alternative will be recommended.